Global Effect of Indole-3-Acetic Acid Biosynthesis on Multiple Virulence Factors of Erwinia chrysanthemi 3937 - Yang, Shihui (American Society for Microbiology, 2007)
Production of the plant hormone indole-3-acetic acid (IAA) is widespread among plant-associated microorganisms. The non-gall-forming phytopathogen Erwinia chrysanthemi 3937 (strain Ech3937) possesses iaaM (ASAP16562) and iaaH (ASAP16563) gene homologues. In this work, the null knockout iaaM mutant strain Ech138 was constructed. The IAA production by Ech138 was reduced in M9 minimal medium supplemented with l-tryptophan. Compared with wild-type Ech3937, Ech138 exhibited reduced ability to produce local maceration, but its multiplication in Saintpaulia ionantha was unaffected. The pectate lyase production of Ech138 was diminished. Compared with wild-type Ech3937, the expression levels of an oligogalacturonate lyase gene, ogl, and three endopectate lyase genes, pelD, pelI, and pelL, were reduced in Ech138 as determined by a green fluorescent protein-based fluorescence-activated cell sorting promoter activity assay. In addition, the transcription of type III secretion system (T3SS) genes, dspE (a putative T3SS effector) and hrpN (T3SS harpin), was found to be diminished in the iaaM mutant Ech138. Compared with Ech3937, reduced expression of hrpL (a T3SS alternative sigma factor) and gacA but increased expression of rsmA in Ech138 was also observed, suggesting that the regulation of T3SS and pectate lyase genes by IAA biosynthesis might be partially due to the posttranscriptional regulation of the Gac-Rsm regulatory pathway.